The Function of Messages in Organizational Communication in the Establishment of the Media Production Study Program - Nur Afni Rachman; Enik Rukiati (P3M Politeknik Negeri Jember, 2023)
One of the current needs of the labor market and stakeholders in Politeknik Negeri Jember is a study program under the communication discipline, namely Media Production. In order to realize the new study program in media production, Politeknik Negeri Jember appointed a task force team to establish the Media Production Study Program. This task force worked together to make the proposals for establishment of the new study program. The results of the literature study show that the flow of communication took place from top to bottom. The flow of communication activity brought messages to be delivered to the recipients. There were three message functions carried out in this activity, namely task messages, maintenance messages, and update messages. There were also three communications that were used, namely vertical downward communication, upward vertical communication, and horizontal communication. The recent study tried to elaborate those three message functions and usages. This study utilized a qualitative paradigm, with no intention of carrying out hypothesis testing, generalization, and is intersubjective. Moreover, this research was a descriptive research that focuses on a systematic, factual and accurate description of the facts.